From the delta to the cataract : studies dedicated to Mohamed el-Bialy - Jiménez Serrano, Alejandro.; Pilgrim, Cornelius von.; El-Bialy, Mohamed, 1953- (Culture and History of the ancient Near East ;, 2015)
"This volume in honour of Mohamed el-Bialy offers 22 contributions by his friends and colleagues in appreciation for many years of true cooperation during his long career in Egyptian archaeology. The articles deal with a wide range of topics and cover a time span from prehistory to the Byzantine Era. Unpublished objects and texts as well as results of most recent field research are presented by leading scholars in archaeology, Egyptology, architectural history and religious studies. The focus on the regions of Aswan and ancient Thebes reflects the particular research interests of the honoree and his constant efforts to protect the archaeological heritage at these two centers of ancient Egyptian civilization"--Provided by publisher.